Effect of adding Manganese chloride and Co-enzymes (α-lipoic acid and Q10) on post-cryopreservation semen quality characteristics of Holstein bulls: Eidan, S.M.1; Sultan, O.A.A.1; Ibrahim, F.F.2; Hurish, K.F.2 and Naseer, H.H.2 - M., Eidan S. (The Iraqi Journal of Veterinary Medicine, 2018)
This study was undertaken to explore the adding effect of manganese chloride (MnCl2), co-enzyme Q10 (Co-Q10) as well as α-lipoic acid to Tris extender on Freeze ability of Holstein bulls’ semen. This study was carried out at the department of artificial insemination at the Directorate of Animal Resource, Ministry of Agriculture in Abu-Ghraib, Baghdad for the duration from October 2013 to Jun 2014, including three experiments. Seven Holstein bulls of 3.5-4 years old were used in this study. Semen was collected via artificial vagina by one ejaculate/ bull/ week. The assessments were conducted for fresh semen, which was later pooled, equally divided for various treatments within each experiment, using Tris extender. In the first experiment, pooled semen was divided into three groups. First group was diluted with Tris only. Manganese chloride was added to Tris extender (0.7 mM) in the 2nd group while in 3rd group (0.9 mM) of the Manganese chloride was used. In the second experiment, semen was divided equally into three groups. The first group was considered as a control group diluted with Tris only. Co-enzyme Q10 was added to 2nd (0.2 mM) and 3rd groups (0.5 mM) treatments respectively. In the third experiment, semen was divided into three groups. The first group was diluted with Tris only (control group). While the 2nd and 3rd groups were added 0.5 and 1.0 mM α-lipoic acid respectively. The effect of these additions on Holstein bulls semen quality was studied during different periods (48 hours, one, two and three months post cryopreservation) for three experiments. The results revealed that the addition two levels of the MnCl2 (2nd and 3rd, experiment 1), Co- Q10 (2nd and 3rd, experiment 2) and α- lipoic acid (2nd and 3rd experiment 3) led to significant increases freezability as compared with control groups during all the experiment periods. In conclusion, the addition of MnCl2, Co-Q10 and α-lipoic acid led to improved post-cryopreservation semen quality of Holstein bulls. This will in turn enhance fertility rate of artificially-inseminated cows and owners economic income consequently.